2021
DOI: 10.1371/journal.pone.0253053
|View full text |Cite
|
Sign up to set email alerts
|

Musical instrument engagement across the life course and episodic memory in late life: An analysis of 60 years of longitudinal data from the Wisconsin Longitudinal Study

Abstract: Background As the global burden of dementia increases, the absence of treatment underscores the need for identification of factors that may improve cognitive reserve–the ability to stave off cognitive decline in old age. The beneficial association between musical instrument engagement and episodic memory has been identified in children, young adults, and older adults. Yet, previous studies in musical instrument engagement have rarely examined the potential for adolescence and adulthood exposures to independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In contrast, participants with musical activity did not differ from controls in the domain of learning and memory, although this must be perceived as an essential cognitive skill involved in playing a musical instrument ( Talamini et al, 2017 ). Some correlational studies have reported that musical activity is indeed associated with better episodic memory in OA ( Hanna-Pladdy and MacKay, 2011 ; Gooding et al, 2014 ; Mansens et al, 2018 ; Romeiser et al, 2021 ), while others do not find such effects ( Hanna-Pladdy and Gajewski, 2012 ; Fauvel et al, 2014b ; Strong and Mast, 2019 ). Taken together, our findings in OA substantiate that musical activity may predominantly favor cognitive abilities involving the frontal lobe.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, participants with musical activity did not differ from controls in the domain of learning and memory, although this must be perceived as an essential cognitive skill involved in playing a musical instrument ( Talamini et al, 2017 ). Some correlational studies have reported that musical activity is indeed associated with better episodic memory in OA ( Hanna-Pladdy and MacKay, 2011 ; Gooding et al, 2014 ; Mansens et al, 2018 ; Romeiser et al, 2021 ), while others do not find such effects ( Hanna-Pladdy and Gajewski, 2012 ; Fauvel et al, 2014b ; Strong and Mast, 2019 ). Taken together, our findings in OA substantiate that musical activity may predominantly favor cognitive abilities involving the frontal lobe.…”
Section: Discussionmentioning
confidence: 98%
“…For example, lower initial cognitive performance, lower socioeconomic status (Román-Caballero et al, 2021a), higher body mass index (Xue et al, 2019), or higher baseline levels of anxiety and depression (Williams & Lord, 1997) are conditions that have been linked with greater benefits in musical training and physical activity, presumably due to a greater window of opportunity. Situations of cognitive vulnerability, such as aging (Chen et al, 2020;Román-Caballero et al, 2018;Romeiser et al, 2021) and brain disorders (Dauwan et al, 2021), also benefit more than people in an optimal state of functioning. And when studied in children and adolescents, the younger participants incur greater benefits (Román-Caballero et al, 2021a;Sanabria et al, 2019).…”
Section: Identification Of Moderator Variablesmentioning
confidence: 99%
“…While there are clearly many investigations in the literature comparing musicians and nonmusicians, fewer break the dichotomy down into different types of musicianship and when they do, the results are often mixed. For instance, some studies have compared professional to amateur musicians and nonmusicians ( Kauffman and Carlsen, 1989 ; Gaser and Schlaug, 2003 ; Hove et al, 2010 ; Krause et al, 2010 ; Repp, 2010 ; Mikutta et al, 2014 ; Appelgren et al, 2019 ), early- vs. late-trained musicians ( Watanabe et al, 2007 ; Bailey and Penhune, 2010 , 2013 ; Steele et al, 2013 ; Bailey et al, 2014 ; Shenker et al, 2022 ), and active vs. inactive musicians ( Hanna-Pladdy and Gajewski, 2012 ; Bonde et al, 2018 ; Romeiser et al, 2021 ). This last classification of active vs. inactive musicians is especially important for investigating how ingrained these musical abilities truly are—do they dull without regular maintenance or are they set in stone once perfected?…”
Section: Introductionmentioning
confidence: 99%